2014Childrens Studies Education Fishermen In Kanagarian Sasak Sasak District of West Pasaman Pasisie Domains, Thesis - CAN, IRFAN; Drs. Edi Suarto, M.Pd, Drs. Edi Suarto, M.Pd; Despica, S.Pd., M.Si, Rika (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research study aims to find out about the education of children of fishermen in the District Sasak Sasak Kanagarian Pasisie Pasaman West Domains, which is where the parents met the low motivation of parents both lower economic third neighborhood is also low. That led to the children in many low Sasak Kanagarian pendidikanya due to several factors. Education is very important role for children of fishermen to make children responsible and useful to the nation.Qualitative research with a snowball technique (snowball). It starts with selecting informants and conducting interviews of the person, then requested referral, advice, guidance informant who should be the next who have the knowledge, experience, information on the search and to then performed in the same manner so as to obtain a lot of information.Based on the discovery and discussion of the results of this study are as follows: First morivasi parents who are in Kanagarian Sasak expressed less so berdamapak for childrens education. Both parents are less economic contained in Sasak Kanagarian very pendididkan impact on children, despite parents work as fishermen but its income is inadequate to meet the day-to-day life so stout neglected childs education. Third Sasak Kanagarian environment affect childrens education, influenced by peers who are not in school and terkilogi influence in modern times.Â